Youth-caregiver Agreement on Clinical High-risk Symptoms of Psychosis - Golembo-Smith, Shana (2014)
Early identification of individuals who will go on to develop schizophrenia is a difficult endeavor. The variety of symptoms experienced by clinical high-risk youth make it difficult to identify who will eventually develop schizophrenia in the future. Efforts are being made, therefore, to more accurately identify at-risk individuals and factors that predict conversion to psychosis. As in most assessments of children and adolescents, however, both youth and parental report of symptomatology and resulting dysfunction are important to assess. The goals of the current study were to assess the extent of cross-informant agreement on the Structured Interview for Prodromal Symptoms (SIPS), a widely-used tool employed to determine clinical high-risk status. A total of 84 youth-caregiver pairs participated. Youth and caregiver raters displayed moderate overall agreement on SIPS-rated symptoms. Both youth and caregiver ratings of youth symptomatology contributed significantly to predicting conversion to psychosis. In addition, youth age and quality of youth-caregiver relationships appear to be related to cross-informant symptom ratings. Despite differences on individual SIPS domains, the majority of dyads agreed on youth clinical high-risk status. Results highlight the potential clinical utility of using caregiver informants to determine youth psychosis risk.